2016
DOI: 10.1111/imre.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Residential Concentration on Voter Turnout among Ethnic Minorities

Abstract: Utilizing a large and unique dataset composed of government records, we study the widely contested effect of co‐ethnic residential concentrations on voter turnout. Non‐Western immigrants are moderately affected by the concentration of co‐ethnic voters in their neighborhoods. As the local concentration of same‐ethnicity voters increases, so does the individual's propensity to turn out for the election. In general, the concentration of non‐Western immigrants in the neighborhood has only a very limited impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 35 publications
1
20
0
1
Order By: Relevance
“…While scholars have paid considerable attention to explaining why some groups-in particular those with higher education and income levels-participate more than others, an emerging dividing line in political activity in most Western European societies has received much less scholarly attention: the one between the children of immigrants and the majority population. This is partly because of a lack of data, and partly because existing theories fall short in addressing the particular political environment minority youths face in contemporary Europe.With some cross-country variation, children of immigrants turn out to vote at substantially lower levels than their majority peers (Herzog-Punzenberger et al 2012, 199;Bhatti and Hansen 2017). In the Danish case that I analyze, a series of studies since 1997 have demonstrated that not only do the children of immigrants turn out to vote less than majority Danes, their electoral participation is even lower than that of immigrants (Elklit et al 2004;Bhatti and Hansen 2010;Bhatti et al 2014;2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While scholars have paid considerable attention to explaining why some groups-in particular those with higher education and income levels-participate more than others, an emerging dividing line in political activity in most Western European societies has received much less scholarly attention: the one between the children of immigrants and the majority population. This is partly because of a lack of data, and partly because existing theories fall short in addressing the particular political environment minority youths face in contemporary Europe.With some cross-country variation, children of immigrants turn out to vote at substantially lower levels than their majority peers (Herzog-Punzenberger et al 2012, 199;Bhatti and Hansen 2017). In the Danish case that I analyze, a series of studies since 1997 have demonstrated that not only do the children of immigrants turn out to vote less than majority Danes, their electoral participation is even lower than that of immigrants (Elklit et al 2004;Bhatti and Hansen 2010;Bhatti et al 2014;2016).…”
mentioning
confidence: 99%
“…This is partly because of a lack of data, and partly because existing theories fall short in addressing the particular political environment minority youths face in contemporary Europe.With some cross-country variation, children of immigrants turn out to vote at substantially lower levels than their majority peers (Herzog-Punzenberger et al 2012, 199;Bhatti and Hansen 2017). In the Danish case that I analyze, a series of studies since 1997 have demonstrated that not only do the children of immigrants turn out to vote less than majority Danes, their electoral participation is even lower than that of immigrants (Elklit et al 2004;Bhatti and Hansen 2010;Bhatti et al 2014;2016). In addition, the minority/majority gap has widened since 1997-amounting to thirty-seven percentage points in 2015-even though minority youths are advancing their incorporation in other domains of society, e.g., education (Fallesen 2017;Bhatti and Hansen 2017).…”
mentioning
confidence: 99%
“…Low levels do not provide these resources. Bhatti and Hansen (2016) find effects of ethnic residential concentration on voter turnout once the concentration becomes a critical mass. Dancygier (2017) finds a similar effect on preferential voting in areas of high concentration of Muslims in Belgian municipalities.…”
Section: Beyond Composition: Immigrant Concentration Effects On Bloc mentioning
confidence: 93%
“…These correlations are not found at low rates of immigrant concentration. Bhatti and Hansen (2016) observe effects of ethnic residential concentration on voter turnout once the concentration becomes a critical mass. Finally, Dancygier (2017) only finds a similar effect on preferential voting for candidates of the same immigrant background in areas of high Muslim immigrant concentration in Belgian municipalities.…”
Section: Factors Explaining Support For Denk: Embeddedness In Immigramentioning
confidence: 97%